Dynamics of the students’ physical fitness while studying at higher educational institutions - Grokhova, G. (My University, 2020)
The article presents an analysis of the dynamics of the students’ physical fitness while studying at Ukrainian higher educational institutions. The level of physical fitness was assessed by the results in exercises that characterize the development of basic physical qualities: speed qualities (100 m run), speed and power qualities (long standing jump), power qualities (pull-ups, push-ups, and sit-ups for males; flexed arm hang, push-ups, and sit-ups for females), endurance (3000 m run for males and 2000 m run for females), flexibility (bending forward from a sitting position), agility (4 x 9 m shuttle run). The study was conducted in Polissia National University in 2013-2019. 16 groups of the students from the faculties of economics, agronomy, ecology, technology, agricultural management, and agriculture mechanization took part in the study; in total, the research involved 369 students, including 195 males and 174 females. The research methods included the analysis and generalization of scientific, educational and methodical literature on physical education, the methods of conceptual and comparative, system and structural analysis, pedagogical observation, testing, the methods of statistical data processing.
Keywords: physical education; physical fitness; physical qualities